(untitled) (International Journal of Engineering and Computer Science, 2018)
Cryptography is the art of secret writing. Data encryption means that only a person having the secret code or key can read scrambled information. The important role of cryptography is to provide the security to the wireless networks. Over the years, many encryption techniques have been provided and used. The conventional methods of encryption can only preserve the data. Developing the new concept in cryptography is a demand of the current time, because the modern cryptography is very much needed to boost the data security. Therefore, it is necessary to relate efficient encryption technique to boost data security. This paper discusses different historical cryptography techniques, modern encryption algorithms (symmetric and asymmetric), and newer areas that are being explored in cryptography. This paper also explores its applications in network security.